Sudden Surges and Macroprudential Policies - Bandaogo, Mahama Samir; Lartey, Emmanuel K.K. (Taylor and Francis, 2021)
This paper estimates the unconditional probability of a sudden surge in private credit and investigates the extent to which macroprudential policies impact the duration of the period preceding such a surge. While we observe sudden surges of credit over periods in which macroprudential policies were enacted, we document that these policies were effective at lowering the probability of credit booms between 2000 and 2013.